Establishment and validation survival prediction models for T1 locally advanced breast cancer after breast conservation surgery versus mastectomy - Fang Qian; Haoyuan Shen; Chenghao Liu; Dongtao Liu; Wei Chen (Scientific Reports)
Abstract Previous reports have indicated that the survival rate of total mastectomy (TM) is higher than that of breast-conserving surgery (BCS). This study established survival prediction models for T1-stage locally advanced breast cancer (LABC) comparing TM and BCS, aiming to identify risk factors for overall survival (OS) associated with different surgical approaches and provide a basis for individualized treatment by clinicians. Cases of pathologically confirmed T1 LABC between 2010 and 2015 were retrieved from the Surveillance Epidemiology and End Results (SEER) database. COX regression analysis was used to analyze the relationship between LABC TM, BCS and various factors. Hazard ratio (HR) and 95% confidence interval (95%CI) were calculated to determine the possible influencing factors. Significant factors from multivariate COX regression were included into the models construct nomograms. Receiver operating characteristic curves (ROC), area under the curve of ROC (AUC), calibration curves, and the Hosmer-Lemeshow goodness-of-fit test for the calibration curves were generated. Model validation was conducted in a separate validation group. The results of COX regression analysis on survival rates for T1 LABC patients undergoing TM and BCS showed that the 5-year overall survival (OS) and breast cancer-specific survival (BCSS) were higher in the BCS group compared to the TM group. Age, race, histological grade, N stage, molecular subtype, chemotherapy, and radiation therapy (RT) were associated with 5-year OS of BCS. Similarly, age, race, pathological type, histological grade, human epidermal growth factor receptor 2 (HER2) status, N stage, molecular subtype, chemotherapy, and RT were correlated with 5-year OS of TM. Prediction nomograms were established using the aforementioned predictors, resulting in AUCs of 0.743 (for 5-year OS of BCS) and 0.718 (for 5-year OS of TM) in the modeling group. Both models were well-validated in the validation group. This study found that the survival rate of the BCS group was higher than that of the TM group, indicating that tumor size determines the survival rate of BCS to some extent. Lymph node status cannot be considered a contraindication for BCS surgery, suggesting that BCS can be considered for LABC patients with smaller tumors and more lymph node metastases. However, patients with primary tumors in N3 stage, triple-negative, and inner upper quadrant have a higher risk of death after BCS compared to other groups, so BCS should be carefully considered for these patients.